2020
DOI: 10.1103/physreva.101.022331
|View full text |Cite
|
Sign up to set email alerts
|

Reverse quantum annealing of the p -spin model with relaxation

Abstract: In reverse quantum annealing, the initial state is an eigenstate of the final problem Hamiltonian and the transverse field is cycled rather than strictly decreased as in standard (forward) quantum annealing. We present a numerical study of the reverse quantum annealing protocol applied to the p-spin model (p = 3), including pausing, in an open system setting accounting for dephasing in the energy eigenbasis, which results in thermal relaxation. We consider both independent and collective dephasing and demonstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…That the empirical total success probability is 1 in this case shows that the p = 2 problem is easy also for forward annealing, in contrast to the p = 3 case studied in Ref. [46], which numerically found very small values of success probability near s inv = 0. This may be explained by the very fast forward annealing in this parameter region in Ref.…”
Section: Total Success Probabilitymentioning
confidence: 46%
See 3 more Smart Citations
“…That the empirical total success probability is 1 in this case shows that the p = 2 problem is easy also for forward annealing, in contrast to the p = 3 case studied in Ref. [46], which numerically found very small values of success probability near s inv = 0. This may be explained by the very fast forward annealing in this parameter region in Ref.…”
Section: Total Success Probabilitymentioning
confidence: 46%
“…This may be explained by the very fast forward annealing in this parameter region in Ref. [46], which keeps the system almost unchanged from the quantum-disordered state at s = s inv . Aside from this subtlety, our experimental data are consistent with the numerical results of Ref.…”
Section: Total Success Probabilitymentioning
confidence: 94%
See 2 more Smart Citations
“…The annealing is performed backward from the known classical state to a state of quantum superposition, then proceeding forward it is possible to reach a new classical state that is a better solution than the initial one. Recently, it has been shown that it is possible to refine local solutions with recursive applications of reverse annealing [65][66][67][68]. We believe that the development of hybrid quantum-classical methods, such as mentioned above, will be essential to solve complex seismic problems on quantum annealers in the near future.…”
Section: Discussionmentioning
confidence: 99%